2021
DOI: 10.1002/cld.1107
|View full text |Cite
|
Sign up to set email alerts
|

More Than Meets the Eye?

Abstract: A 37-year-old African American man with a history of primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), and ulcerative colitis (UC) presented to the emergency department with jaundice and fatigue. He was originally diagnosed with PSC on the basis of magnetic resonance cholangiopancreatography (MRCP) 8 years ago. He subsequently had increasing aspartate aminotransaminase (AST) and alanine aminotransferase (ALT) 1 year prior to his current presentation with ALT 145 U/L, AST 92 U/L, alkaline phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that time to onset in idiosyncratic cholestatic liver injury cases was generally within a few months and rarely exceeded 6 months of azathioprine initiation or dose increase. 3 , 5 We present a case with symptomatic and clinically significant cholestatic ALI multiple years after azathioprine initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that time to onset in idiosyncratic cholestatic liver injury cases was generally within a few months and rarely exceeded 6 months of azathioprine initiation or dose increase. 3 , 5 We present a case with symptomatic and clinically significant cholestatic ALI multiple years after azathioprine initiation.…”
Section: Introductionmentioning
confidence: 99%